Upper limb lymphedema related to breast cancer therapy: incidence, risk factors, diagnostic techniques, risk reduction and optimal management - Saleh, Hatem A.; Rageh, Tarek M.; Alhassanin, Suzan A.; Megahed, Mohamed A. (International Surgery Journal, 2018)
Background: Lymphedema remains to be a great source of morbidity for breast cancer survivors. The aim of this work is to study upper limb lymphedema following breast cancer therapy for breast cancer patients regarding its incidence, risk factors, diagnostic techniques, risk reduction and optimal management. Methods: This prospective study was done on two hundred breast cancer patients who underwent breast cancer management. The study was done in the period between May 2016 and July 2018. Exclusion criteria were Male patients, Female patients with metastatic breast cancer and who already had upper limb lymphedema before breast cancer management. All patients underwent follow up for incidence, risk factors, diagnostic techniques and management of lymphedema. Statistical analysis used: The collected data were organized, tabulated and statistically analyzed using SPSS software Results: The incidence of lymphedema was (18 %) distributed as follow: grade I = 55.6%, grade II = 33.3%, grade III = 11.1 % and grade IV = 0 %. The most relevant risk factors for development of lymphedema were: age between 41 and 50 years and diabetes mellitus. Higher incidence of pain (66.7%) and restricted motion (61.1%) were observed in lymphedema cases. Conclusions: Old (41:50 years) and diabetic patients are at the highest risk for developing lymphedema. Breast cancer patients of stage IIIB who had undergone modified radical mastectomy or who developed postoperative seroma are at higher risk for developing lymphedema. Physical exercises and compression garment are important part of treatment plan.